Reimagining public anthropology in Finland - Niina Ahola; Saara Toukolehto (Suomen Antropologi)
Broadly speaking, public anthropology is understood to signify the dissemination of anthropological knowledge beyond academic circles, but no clear definition yet exists. The article takes part in the discussion on what public anthropology is and how it might be promoted through the case study of the online publication AntroBlogi.fi. The article approaches public anthropology through six modes of knowledge sharing derived from AntroBlogi’s portfolio: popularising academic research, applied knowledge, social commentary, light entertainment, multidisciplinary meaning-making, and awareness creation. Through these modes, it is shown what successful public anthropology might look like. It is argued that anthropology can be popularised without compromising academic rigour. Towards this end, it is suggested that it is worthwhile to approach the concept of public anthropology with the same analytical ambition as other central concepts of the discipline. Only by advancing public anthropology inside academia can it be effectively promoted outside of it.